272 DETECTION, ANALYSIS AND SIGNIFICANCE OF GUANYLYL CYCLASE C IN THE LYMPH NODES FROM PATIENTS WITH COLORECTAL CANCER. (1st January 2006) - Tang, C.; Wu, A.; Leong, E.; Fears, T.; Azzi, R.; O'Shannessy, D.; Lin, A.
Abstract : Purpose: Colorectal cancer (CRC) is one of the top leading causes of cancer-related mortality in the United States and worldwide. Guanylyl cyclase C (GCC) is a receptor that mediates fluid and electrolyte secretion and is expressed only in mucosal cells lining the intestine but not by other extraintestinal tissues. Expression of GCC has been used for the detection of colorectal carcinoma. Recent studies have identified detectable GCC in the peripheral blood from patients diagnosed with CRC. This study was designed to correlate the significance of GCC expression in lymph nodes from CRC patients with clinical outcomes. Methods Used: Paraffin-embedded lymph nodes (PELN) were obtained for analysis under an institutional review board-approved protocol from 103 CRC patients (stage I: 11%; stage II: 31%; stage III: 34%; stage IV: 23%; median follow-up 3.4 years, range 0.1-12.1 years). The male to female ratio was 57:46. Follow-up information was obtained from hospital tumor registry and RT-PCR assays were performed in 273 PELN blocks. Kaplan-Meier methods were used to estimate overall survival. Cox proportional hazard models were used for univariate as well as multivariate analyses. Results: The Spearman coefficient of correlation between the expression of GCC and clinical stage was 0.67 ( p < .01). Survival was associated with clinical stage (p < .001) and GCC expression (p < .01) but not chemotherapy (p = .44) or tumor grade (p = .11). Conclusion: GCC expression by RT-PCR assay of the lymph nodes significantly correlates with clinical stage. In addition to clinical stage, its expression in the lymph nodes is associated with survival in patients with CRC. Further studies with a larger sample size are needed to confirm these findings.